Pre-Procedural C-Reactive Protein Level Predicts In-Hospital Outcome in Percutaneous Coronary Intervention - Haque, MM; Ullah, M; Alam, MS; Ulabbi, SU; Uddin, R (Cardiovascular Journal, 2012)
Background:To accurately stratify patients undergoing PCI, according to their risk of future adverse events, a quest for risk predictors is ongoing worldwide. But only a few powerful and independent predictors of early and late major adverse cardiovascular events have been found. These include traditional risk factors, such as acute coronary instability, diabetes mellitus, reference vessel diameter, and lesion and/or stent length. This study was undertaken to find out the relationship between pre-procedural CRP level with in-hospital (both procedural and before discharge) complications. Materials & methods: This prospective study was carried out in National Institute of Cardiovascular Diseases (NICVD), Dhaka during the period of June,2006 to May,2007. After fulfilling the exclusion criteria, 100 consecutive patients were selected as sample those underwent percutaneous coronary intervention. C-Reactive protein (CRP) was measured in all patients before the procedure. Those having pre-procedural CRP level <.3 mg/dl was labeled as group-I and those with CRP level e”.3 mg/dl was labeled as group-II. In hospital outcomes were compared between two groups after percutaneous coronary intervention. Results: During the procedure, higher rate of complications (10.0% vs 26.0%) were noted in group- II, which was statistically significant. Among many complications abrupt occlusion, threatened (dissection and new thrombus) and residual stenosis were significantly high in group-II. Other complications like coronary spasm, arrhythmia, side branch occlusion, heart failure, shock and no reflow were also high in higher level of CRP level patients but statistically not significant. Inhospital complications were also significantly high (10.0% vs 28.0%) in patients with higher level of CRP ie. Group-II. Among other complications recurrence of ischemia and myocardial infarction developed at significantly higher rate in group-II. Post procedural CK-MB rose significantly (18.0% vs 36.0%) in patients with higher level of CRP (group-II) in comparison to normal level of CRP patients (group-I). When the in-hospital complications were distributed among three tertiles of CRP, it was observed that complications were proportionately high with increasing level of CRP. Conclusions: Many studies, conducted abroad, have suggested that factors like gender, extreme age, diabetes, multi-vessel disease and lesion characteristics adversely influence PCI outcome. But in this study, multivariate regression analysis has shown that elevated level of CRP is even stronger independent predictor of PCI outcome. Keywords: C-Reactive Protein; In hosital outcome; PCI. DOI: http://dx.doi.org/10.3329/cardio.v4i1.9387 Cardiovasc. J. 2011; 4(1): 32-41